Influence of the intra-peritoneal segment of the swan neck peritoneal catheter on infectious and mechanical complications and technique survival - Banin, Vanessa Burgugi [UNESP]; Ponce, Daniela [UNESP]; Dias, Dayana Bitencourt [UNESP]; de Oliveira, Rogério Carvalho [UNESP]; Martin, Luis Cuadrado [UNESP]; de Moraes, Thyago Proença [UNESP]; Barretti, Pasqual [UNESP] (Springer Nature, 2018)
Background: There is no consensus about the preferable type of catheter for successful peritoneal dialysis. Intra- and extra-peritoneal catheter configuration may be associated with mechanical and infectious complications affecting technique survival. The objective of this study was to compare the mechanical and infectious complications of coiled versus straight swan neck (SN) peritoneal dialysis catheters. Methods: A prospective randomized trial was performed to compare mechanical (tip migration with dysfunction) and infectious (peritonitis and exit site infection) complications between catheters randomly divided into two groups: swan neck straight tip and swan neck coiled tip. The follow-up was 1 year. Results: A total of 49 catheters, in 46 patients, were included from April 2015 to February 2016. The catheters groups were constituted as: 25 coiled tip SN and 24 straight tip SN. The baseline demographics were similar among the groups. Kaplan–Meier survival estimates were not different for time to first exit site infection, peritonitis and time to first catheter tip migration (log-rank test, p = 0.07, p = 0.54 and p = 0.83, respectively). Catheter survival and method survival were also similar (log-rank p = 0.88 and p = 0.91, respectively). Conclusions: The two types of intra-peritoneal segments of SN catheters studied presented similar infectious and mechanical rates with no differences in catheter and technique survival curve. These results were consistent with the recommendations of the International Society for Peritoneal Dialysis.
Keywords: Catheter migration; Peritoneal dialysis; Peritonitis; Swan neck